3D‐Printed Structural Pseudocapacitors. Issue 9 (13th October 2016) - Liu, Xinhua; Jervis, Rhodri; Maher, Robert C.; Villar‐Garcia, Ignacio J.; Naylor‐Marlow, Max; Shearing, Paul R.; Ouyang, Mengzheng; Cohen, Lesley; Brandon, Nigel P.; Wu, Billy
Abstract : Direct metal laser sintering is used to create 3D hierarchical porous metallic scaffolds which are then functionalized with a co‐electrodeposition of MnO2, Mn2 O3, and doped conducting polymer. This approach of functionalizing metal 3D printed scaffolds thus opens new possibilities for structural energy storage devices with enhanced performance and lifetime characteristics.